DIALYSIS PATIENTS LIFE QUALITY: A LITERATURE SYSTEMATIC REVIEW (Fiep Bulletin - online, 2012)
Introduction: chronicle renal diseases claim for attention, especially due to the therapeutic instituted in the present, which reverberate in various changes and difficulties in the substitution renal therapy patient routine. Objective: to know the dialysis repercussions over chronicle renal patients' life quality. Methodology: of 312 articles published and previously identified, were selected 9 articles about dialysis patients' life quality. All the chosen ones were submitted to the methodological approaching of a systematic review. Results: showed that the publications selected found life quality damage due to the dialysis. Conclusion: by evidence is reinforced the urgency in fomenting improvements in patient life conditions, reverberating life quality scores more positive ones.
Keywords: Chronicle Renal Disease; Dialysis; Life Quality.